Use of Emotional and Neutral Speech in Evaluating Compression Speeds - Korhonen, Petri; Kuk, Francis; Slugocki, Christopher; Davis-Ruperto, Neal (Journal of the American Academy of Audiology, 2021)
Background Emotional speech differs from neutral speech in its envelope characteristics. Use of emotional speech materials may be more sensitive for evaluating signal processing algorithms that affect the temporal envelope.Purpose Subjective listener preference was compared between variable speed compression (VSC) and fast acting compression (FAC) amplitude compression algorithms using neutral and emotional speech.Research Design The study used a single-blinded, repeated measures design.Study Sample Twenty hearing-impaired (HI) listeners with a bilaterally symmetrical, mild- to-moderately severe sensorineural hearing loss and 21 listeners with normal hearing (NH) participated.Intervention Speech was processed using FAC and VSC algorithms.Data Collection and Analysis A paired-comparison paradigm assessed subjective preference for FAC versus VSC using emotional and neutral speech materials. The significance of subjective preference for compression algorithm (FAC or VSC) was evaluated using a linear mixed effects model at each combination of stimulus type (emotional or neutral speech) and hearing group (NH or HI).Results HI listeners showed a preference for VSC over FAC when listening to emotional speech. The same listeners showed a nonsignificant, preference for VSC over FAC when listening to neutral speech. NH listeners showed preference for VSC over FAC for both neutral and emotional speech materials.Conclusion These results suggest that the subjective sound quality of emotional speech is more susceptible than neutral speech to changes in the signal introduced by FAC. Clinicians should consider including emotional speech materials when evaluating listener preference for different compression speeds in the clinic.
Keywords: hearing aids; compression; emotions; sound quality